Shrinkage of moldings and injection molding conditions - Postawa, P. (Polimery, 2022)
Results of experiments focused on assessment, in injection molding, of the effects of independent variables (input parameters) on dependent variables: longitudinal shrinkage (Sw), perpendicular shrinkage (Sp) (Fig. 2 and 3) and weights (m) of the moldings made of semi-crystalline polyoxymethylene (POM) or amorphous polystyrene (PS) were presented. Experiment design consisted of 27 systems investigated and 5 input parameters: mold temperature (Tf), injection temperature (Tt), clamping pressure (pd), cooling time (tch) and injection speed (vw) (Table 2 and 3). Diversification of values of perpendicular shrinkage along the way of plastic flow in mold cavity (Fig. 4) has been found. Statistic analysis of the results based on estimation of parameters of regression equations (2) describing the variability of dependent values investigated as the functions of independent variables (Table 6). Analysis of correlation was done as well and the results were presented in the form of matrix of correlation (Table 4 and 5). It results from the data presented that with the aim to control the shrinkage value and molding weight in the industrial practice it is most advantageous to change the clamping pressure as essential easy-to-change parameter.